The role of electronic cigarettes in smoking cessation: an evidence-based review - Couto, Pedro (2015)
Objectives: To determine if electronic cigarettes are effective in smoking cessation. Data sources: MEDLINE databases; National Clearinghouse; Canadian Medical Association Practice Guidelines InfoBase; Guidelines Finder of the National Electronic Library for Health in the British NHS; Database of Abstracts of Reviews of Effectiveness – Centre for Reviews and Dissemination; Bandolier; The Cochrane Library; Index of Portuguese Medical Journals. Review methods: Articles published between 01/07/2004 and 30/06/2014 using the MeSH term ‘smoking cessation’, the English terms ‘electronic cigarette(s)’, ‘e-cigarette(s)’, ‘e-cig(s)’ and the Portuguese terms ‘cessação tabágica’ and ‘cigarro(s) ele(c)trónico(s)’. Studies that evaluated the smoking cessation in smokers exposed and not exposed to electronic cigarettes were included. ‘Strength-of-Recommendation Taxonomy’, ‘Jadad’ and ‘Newcastle-Ottawa’ scales were used to assess the quality of the studies and the strength of recommendations. Results: The search produced a list of 2,076 articles. Ten articles were excluded as duplicates, 2,005 were excluded after reading the title because they were not directly related to the topic, 47 were excluded after reading the summary, and 11 after reading the full text because they did not meet the inclusion criteria. Three articles were included in this review. They were a systematic review, which included nine original studies [Level of Evidence (LE) 2], a classic review (LE 3), whose conclusions were unfavorable to the use of electronic cigarettes, and one cross-sectional study, which showed an increased use of electronic cigarettes compared to other therapies among those who stopped smoking (LE 3). Conclusions: Most studies found no association between use of electronic cigarettes and smoking cessation. The authors concluded that its use does not seem to play a beneficial role in smoking cessation (Strength of Recommendation B). Given the rapid expansion and growing popularity of these products, better quality studies are needed.